The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3389/fpubh.2021.706778
|View full text |Cite
|
Sign up to set email alerts
|

Challenges and Barriers Toward Medical Research Among Medical and Dental Students at King Khalid University, Abha, Kingdom of Saudi Arabia

Abstract: Background: Medical research is a systematic method to obtain new knowledge, reduce diagnosis problems, discover the latest or best treatment for a disease, and also used for disease prevention.Objective: The study aims to assess the challenges and barriers to conduct medical research among medical and dentistry students and determine the reasons that hinder the conduct of the study.Methods: In this cross-sectional study, the research population consisted of medical and dental students affiliated with King Kha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 36 publications
(42 reference statements)
6
15
0
Order By: Relevance
“…This finding concurs with that reported by Kyaw and colleagues in Malaysia [ 27 ] and another in Sweden [ 10 ] where students of older age and in higher years of study were more knowledgeable about research than the younger and in lower years of study. It also agrees with various studies that found a higher association between male sex and research involvement [ 24 , 25 ]. However, it contrasts with that reported in Saudi Arabia where age above 25 years was associated with less involvement in research [ 20 ].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This finding concurs with that reported by Kyaw and colleagues in Malaysia [ 27 ] and another in Sweden [ 10 ] where students of older age and in higher years of study were more knowledgeable about research than the younger and in lower years of study. It also agrees with various studies that found a higher association between male sex and research involvement [ 24 , 25 ]. However, it contrasts with that reported in Saudi Arabia where age above 25 years was associated with less involvement in research [ 20 ].…”
Section: Discussionsupporting
confidence: 93%
“…Our finding agrees with those reported by previous studies among medical and Nursing students where more than half of participants reported to be aware about research [ 23 , 24 ] and had positive attitude towards it [ 8 , 24 , 25 ], but in contrast with that by Chellaiyan and colleagues in India [ 26 ] where less than a quarter of students had a positive attitude towards medical research. Such and more programs like research results dissemination conferences aimed at exposing students to research are encouraged to better this awareness and positive attitudes.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our nding agrees with that reported by previous studies where more than half of participants reported to be aware about research (20)(21) and had positive attitude towards it (21)(22), but in contrast with that by Chellaiyan and colleagues in India (23) where less than a quarter of students had a positive attitude towards medical research. Such and more programs such as research results dissemination conferences aimed at exposing students to research are encouraged to better this awareness and positive attitudes.…”
Section: Discussionsupporting
confidence: 92%
“…Other significant barriers included a lack of mentors, a lack of funds, and undergraduate students believing they are unqualified to conduct research. Alsaleem SA et al (2021) [ 18 ] Kingdom of Saudi Arabia Lack of time, skills, funding, facilities, and limited access to medical journals and related databases were the significant barriers found. Kanmounye US et al (2020) [ 19 ] Cameroon Barriers to research included lack of funding, obsolete patient information management systems, and limited understanding of biostatistics.…”
Section: Barriers and Challenges Facing Involvement Of Undergraduate ...mentioning
confidence: 99%